Characteristics and correlation analysis of negative emotions, quality of life, and chinese medicine syndromes in patients with lung cancer after surgery: A cross-sectional study - Cong-Meng Zhang; Yi-Feng Gu; Sheng-Ping Shen; Yi-Chao Wang; Ao Qi; Ling-Zi Su; Jia-Lin Yao; Jia-Qi Li; Wen-Xiao Yang; Qin Wang; Li-Jing Jiao; Xiong Qin; et al. (World Journal of Traditional Chinese Medicine, 2023)
Objective: The objective of the study was to observe and analyze the characteristics of negative emotions and quality of life (QoL) in patients with nonsmall cell lung cancer (NSCLC) from 1 to 3 months after surgery, and summarize their population characteristics after surgery. Materials and Methods: The consolidation rehabilitation period was defined as 1 to 3 months after surgery. The main observation indicators were the general Hospital Anxiety and Depression Scale, the European Organization for the Research and Treatment of Cancer Core QoL Questionnaire (EORTC QLQ-C30), and EORTC QLQ-Lung Cancer-13. The secondary observation indicators were peripheral blood cytokines and immune function indicators. Statistical methods such as one-way analysis of variance and logistic regression were used to analyze the characteristics of this part of the population. Results: Among patients who underwent lung surgery, the overall incidence of anxiety during consolidation recovery was 13.66%, and that of depression was 10.38%. The scores of fatigue, pain, dyspnea, insomnia, and loss of appetite were significantly higher than those of other symptoms (P = 0.000). The presence of anxiety was associated with the site of surgery (P < 0.05) and the presence of depression was associated with emotional functioning and dyspnea (P < 0.05). Conclusions: The occurrence of negative emotions in the postoperative NSCLC population is related to gender, and the degree of emotions is negatively correlated with QoL and positively correlated with the degree of symptoms. The main relevant syndromes are the pulmonary and meridian categories.